Critical Analysis of Healthcare Policy Reform: Addressing Systemic Inequities and Advancing Universal Health Coverage - Al zmanan, Abdullah Hadi Mana; Al monif, Abdullah Hamed Hadi; Al zmanan, Salih Yahia Salih; Alshehri, Fahad Mohammed Jaber; Alshehri, Mohammed Amer Ahmed; Alakkasi, Faris Ibrahem Abduallah; Asiri, Abdulaziz Awad Malahi; Alzubaidi, Abdulelah Hezam Ali; Alshehri, Mohammed Ghaithan Ghurman; Atiah, Hassan Ibrahim Mohammed (Journal of Ecohumanism, 2024)
Healthcare policies have now emerged as important programs globally, especially considering various systemic issues that affect health inequalities for the poor. Healthcare policy reform has now become a critical consciousness globally. As mentioned in the section of the paper, goals, and objectives, following this brief discussion on the targeted inefficiencies and inequities seeking UHC reforms, this paper aims to offer a critical analysis of the reforms that aimed at fulfilling the above-mentioned goals of these changes. There is an implementation gap in UHC globally even though it was designed to ensure that every human being gets access to healthcare services when needed, but they should not be forced to pay for the services Lime and Thorlacius (2017). This paper analyzes the differences between nations with insufficient systems by looking at successful UHC models and comparing them to those of the US, such as Canada, the UK, and Brazil. It also examines new directions in healthcare policies based on new technologies, including digital health, PPPs, and other financing schemes that have been demonstrably effective in removing obstacles to UHC. In assessing these issues about contemporary humanitarian policies and health status, this paper outlines the opportunities and challenges in advancing global healthcare equity. That is why the goal is to outline additional policy reforms based on the literature analysis that can help eliminate inequalities regarding healthcare accessibility, quality, and efficiency.